Long-term use of amiodarone before heart transplantation significantly reduces early post-transplant atrial fibrillation and is not associated with increased mortality after heart transplantation - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Schmack, Bastian; Erbel, Christian; Gleißner, Christian A.; Akhavanpoor, Mohammadreza; Frankenstein, Lutz; Darche, Fabrice Fernand; Schweizer, Patrick Alexander; Thomas, Dierk; Ehlermann, Philipp; et al. (Drug design, development and therapy, 2016)
Amiodarone is a frequently used antiarrhythmic drug in patients with end-stage heart failure. Given its long half-life, pre-transplant use of amiodarone has been controversially discussed, with divergent results regarding morbidity and mortality after heart transplantation (HTX).Aim: The aim of this study was to investigate the effects of long-term use of amiodarone before HTX on early post-transplant atrial fibrillation (AF) and mortality after HTX.
Gesehen am 30.04.2020